Over Disgerminomu - Fidan, Hakan (Ankara Üniversitesi, 1991)
Ender görülen over tümörlerinden olan disgerminomlar, testisin seminomuna benzerlik göstermektedir. Hormonal fonksiyonları tartışmalı olan bu tümörler, özellikle gençlerde görülmekte ve daha sıklıkla sağ overden kaynaklanmaktadır. Çalışmamızda laboratuvarımızda saptadığımız bir disgerminom olgusu sunuldu.

Dysgerminomas of ovary are rarely seen and similer to seminoma of testis. These tumours more İreguentiy originated İrom the right ovary, are reported to be observed in young women and their humoral functions are contraversial. In our study, a dysgerminoma diagnosed in our laboratory was presented.
OVER DİSGERMİNOMU
Keywords: Pathology; Patoloji